MAQASHID SYARIAH DAN PRAKTIK SISTEM PRESIDENTIAL THRESHOLD DI INDONESIA: - Ansori, Saiful Ansori (State of Islamic Institute Langsa, 2020)
This study aims to determine the presidential threshold system in the 2019 simultaneous elections in terms of the perspective of the maqasid shariah. The implementation of the Presidential threshold in the 2019 concurrent elections, the level of benefit and interpretations, including in the dharuriyyah.  aspects. The enactment shows that there is a positive and negative impact, but the election must be continued. This is very important because it involves all aspects of the lives of Indonesian citizens, both in terms of security, protection, religion, culture, economy, law, politics and so on. Then also, the implementation of the Presidential threshold system in the 2019 simultaneous elections, the scope of benefits arising into the category of maqashid al-?Ammah (General maqashid) which is a maqashid which covers all problems contained in the behavior of tashri? 'which are universal such as justice, equality, tolerance, convenience and others, although it was rarely discussed and raised at the research level.